2009
DOI: 10.1016/j.newast.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Possible implications of mass accretion in Eta Carinae

Abstract: We apply the previously suggested accretion model for the behavior of the supermassive binary system η Car close to periastron passages. In that model it is assumed that for ∼ 10 weeks near periastron passages one star is accreting mass from the slow dense wind blown by the other star. We find that the secondary, the less massive star, accretes ∼ 2 × 10 −6 M ⊙ . This mass possesses enough angular momentum to form a disk, or a belt, around the secondary. The viscous time is too long for the establishment of equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 49 publications
5
88
1
Order By: Relevance
“…Even though our simulation does not model the reaction of the secondary and its wind to the accreted mass and its likely feedback on the accreted gas, we measured the amount of mass that reaches the secondary and find it to be in the order of ≈ 10 −6 M⊙ yr −1 , in agreement with the calculations of Kashi & Soker (2009b).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Even though our simulation does not model the reaction of the secondary and its wind to the accreted mass and its likely feedback on the accreted gas, we measured the amount of mass that reaches the secondary and find it to be in the order of ≈ 10 −6 M⊙ yr −1 , in agreement with the calculations of Kashi & Soker (2009b).…”
Section: Resultssupporting
confidence: 73%
“…As the orbital separation increases, accretion rate decreases (Kashi & Soker 2009b), and the secondary wind is expected to resume.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soker et al have discussed in a series of papers an accretion model for η Car, which argues for the opposite effect that we just stated (see, e.g., Soker 2005, Kashi & Soker 2008a2009b). In their scenario, the companion accretes mass from η Car during periastron.…”
Section: Possible Scenarios For the Observed Changes In η Carmentioning
confidence: 56%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%